Obraz młodzieży w filmie– jako impuls do namysłu nad kondycją tożsamości współczesnych nastolatków - Myszka-Strychalska, Lucyna (Wydawnictwo Naukowe UAM, 2017)
The dynamic transformations of the contemporary reality oblige the subject to engage in permanent self-creation and search of their place in the world. Technological development and the increasing role of the pictorial message in socio-cultural life significantlyimpact the individual’s perception of the external environment. A wide filmoffer, an essential element of popular culture, creates both a fictionalimage of the postmodern world and strives to reflectits real image, including the youth participating in its space. In the face of this sketched perspective, a question arises: “To what extent is the image of a young man shown in filmsconsistent with his real face?” and “To what extent does the image of a teenager in a movie affect his own ‘ego’”?
The Picture of Young People in Film as an Impulse to Conside-ring the Condition of the Identity of Modern Teenagers
Keywords: youth; film; present; identit